Pseudopataecus carnatobarbatus, a new species of velvetfish (Teleostei: Scorpaeniformes: Aploactinidae) from the Kimberley coast of Western Australia - Johnson, Jeffrey W. (Zootaxa, 2012)
Pseudopataecus carnatobarbatus, new species, is described from 12 specimens collected on shallow coastal reefs of northernWestern Australia, between the Monte Bello Islands and Adele Island. It is distinguished from its sole congener, P. taenianotusJohnson 2004, by branched (versus simple) tips to most fin rays, last soft dorsal-fin ray joined by membrane more fully toupper caudal-fin ray, spinous dorsal fin more distinctly notched, pelvic fins more robust, anterior face of lower lip smooth (ver-sus profusely covered with cirri), and a narrow quadrangular pit on the forehead, bounded by frontal, supraorbital, ocular andpreocular ridges (versus pit and preocular ridge absent). It also has modally fewer anal-fin rays and modally greater numbers ofgill rakers. Pseudopataecus carnatobarbatus is found in an extremely high tidal range area of Australia, where movement of upto 11 m occurs during spring tides. Specimens were collected in rocky tide pools with coral rubble and thick stands of brownmacroalgae, especially Padina species. The new species has been found in intertidal areas up to only 13 m deep, whereas P. taenianotus has been collected by trawling soft bottom habitats in depths of 20 to 63 m.